If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3e + -72 = -18 Reorder the terms: -72 + -3e = -18 Solving -72 + -3e = -18 Solving for variable 'e'. Move all terms containing e to the left, all other terms to the right. Add '72' to each side of the equation. -72 + 72 + -3e = -18 + 72 Combine like terms: -72 + 72 = 0 0 + -3e = -18 + 72 -3e = -18 + 72 Combine like terms: -18 + 72 = 54 -3e = 54 Divide each side by '-3'. e = -18 Simplifying e = -18
| -214+-8(2x-3)=-334 | | 3v-36=-42 | | 10x+5=12y+5 | | 15y+20= | | 4r+(-12)=48 | | 15y/4=90 | | 2x-6+4x+28=6x+22 | | 3(x+1)x+4(x+3)=22 | | 4(2x-y)=2y+5 | | 147.1875=3r(3.14r^2) | | 0.4(x+25)-3=0.2(7x+10) | | 13x-4x=-63 | | 3y+4z=9fory | | 8x=6y+5 | | 22-6y+y^2-14=0 | | 83=15+2(x) | | -8a=-8b | | (3)(2x-4)+2(2x-4)-x=-17 | | 12=15*Z-1/5 | | x+(-40)=y | | X^2+4x-62.5=0 | | 15=5+9(3) | | b+-4=-4 | | -5x=-5y | | g/3-0.9=-.4 | | 85=17p | | 7x^4z^3/28y^3 | | (6x+2)(3x+4)=64 | | 5y(y+2)= | | -36x-36=0 | | 3(2x+4)-2x=3(2-4x) | | 5[m+4]=-2[-4-m]+3 |